Functional and Phenotypic Changes of Natural Killer Cells in Whole Blood during Mycobacterium tuberculosis Infection and Disease - Garand, Mathieu; Goodier, Martin; Owolabi, Olumuyiwa; Donkor, Simon; Kampmann, Beate; Sutherland, Jayne S. (Frontiers in Immunology, 2018)
Tuberculosis (TB) is still a global health concern, especially in resource-poor countries such as The Gambia. Defining protective immunity to TB is challenging: its pathogenesis is complex and involves several cellular components of the immune system. Recent works in vaccine development suggest important roles of the innate immunity in natural protection to TB, including natural killer (NK) cells. NK cells mediate cellular cytotoxicity and cytokine signalling in response to Mycobacterium tuberculosis (Mtb). NK cells can display specific memory-type markers to previous antigen exposure; thus, bridging innate and adaptive immunity. However, major knowledge gaps exist on the contribution of NK in protection against Mtb infection or TB. We performed a cross-sectional assessment of NK phenotype and function in 4 distinct groups of individuals: TB cases pre-treatment (n = 20) and post-treatment (n = 19), and household contacts with positive (n = 9) or negative (n = 18) tuberculin skin test (TST). While NK frequencies were similar between all groups, significant decreases in interferon-γ expression and degranulation were observed in NK from TB cases pre-treatment compared to post-treatment. Conversely, CD57 expression, a marker of advanced NK differentiation, was significantly lower in cases post-treatment compared to pre-treatment. Finally, NKG2C, an activation and imprinted-NK memory marker, was significantly increased in TST+ (latently infected) compared to TB cases pre-treatment and TST- (uninfected) individuals. The results of this study provide valuable insights into the role of NK in Mtb infection and TB disease, demonstrating potential markers for distinguishing between infection states and monitoring of TB treatment response.